OPTIMIZATION OF THE ANESTHETIC MANAGEMENT OF PATIENTS WITH PERIPHERAL ARTERY DISEASE WHO HAD A LOWER LIMB AMPUTATION - Денис Николаевич Макаров; Сергей Людовикович Кан; Елена Михайловна Васильченко (Медицина в Кузбассе)
The aim of the research – to improve the results of treatment and the survival rate of patients with peripheral artery disease after lower limb amputations by optimizing the anesthetic management during the perioperative period based on studying the risk factors for hospital lethality. Materials and methods. The study included 895 patients. The group of the retrospective study consisted of 654 persons – we studied hospital lethality, the structure of hospital lethality and the risk factors for hospital lethality. The group of the prospective study consisted of 239 persons – we used an algorithm developed by us for the anesthetic management and resuscitation management of patients with lower limb amputations during the perioperative period. Results. We identified eight independent risk factors influencing hospital mortality in lower limb amputations. The use of the algorithm of perioperative management reduced hospital lethality from 8.5 % to 3.4 %, the number of postoperative non-surgical complications from 24.8 % to 9.2 % and the number of postoperative psychoses from 10.5 % to 3.3 %. Conclusions. The independent risk factors that influenced the level of hospital lethality after lower limb amputations in patients with peripheral artery disease are: the level of limb amputation (transfemoral amputation), absence of a previous reconstructive surgery, history of myocardial infarction, concomitant chronic renal insufficiency, baseline level of myoglobin in the blood above 320 ng/ml, baseline level of blood glucose above 8 mmol/l, the need for blood transfusion and the absence of epidural anesthesia during the postoperative period. The use of the algorithm for the anesthetic management of the perioperative period after lower limb amputation in patients with peripheral artery disease showed its effectiveness by a significant reduction in hospital lethality, postoperative complications and postoperative psychoses.